A Novel Double Redundant Brake-by-Wire System for High Automation Driving Safety: Design, Optimization and Experimental Validation - Chao Li (MDPI AG, 2021)
The high redundant brake-by-wire system reveals vehicular safety handling ability and rarely emerges in the automotive area at the present time. This paper presents a novel brake-by-wire system, DREHB (Double Redundant Electro-Hydraulic Brake), with extensible fail-safe operations for high-automation autonomous driving vehicles. The DREHB is designed as a decoupled-architecture system containing three-layer cascaded modules, including a hydraulic power provider, a hydraulic flow switcher, and a hydraulic pressure modulator, and each of the modules can share dual redundancy. The operating principles of the DREHB in normal and degraded initiative braking modes are introduced, especially for the consideration of fail-safe and fail-operational functions. The matching and optimization of selected key parameters of the electric boost master cylinder and the linear solenoid valve were conducted using computer-aided batched simulations with a DREHB system modeled in MATLAB/Simulink and AMESim. The prototype of the DREHB was tested in hardware-in-the-loop experiments. The test results of typical braking scenarios verify the feasibility and effectiveness of the DREHB system, and the hydraulic pressure response as 28.0 MPa/s and tracking error within 0.15 MPa and the desirable fail-safe braking ability fully meets the requirements of higher braking safety and efficiency.